Economic Preferences and Personality Traits Among Finance Professionals and the General Population - Martin Holmen; Felix Holzmeister; Michael Kirchler; Matthias Stefan; Erik Wengström (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Since the financial crisis, the behavior and personality traits of finance professionals have come under scrutiny. As comprehensive scientific findings are lacking, we run artefactual field experiments with finance professionals and a random sample of the working population to investigate differences across industry-relevant economic preferences and personality traits. We report that finance professionals are more risk tolerant, more selfish, less trustworthy, and show higher levels of narcissism, psychopathy, and Machiavellianism. However, we find that many of these differences disappear after adjusting for socioeconomic characteristics, indicating that finance professionals are similar to employees in other industries with a comparable socio-economic background.
Keywords: C93; G11; G41; 330; Experimental finance; economic preferences; personality traits; finance professionals; general working population